EFFECT OF COMPANY INCOME TAX ON INFANT MORTALITY RATE IN NIGERIA (2004-2021) (Journal of Global Accounting, 2022)
This study determined the effect of company income tax on infant mortality in Nigeria. The research is a causal design based on an in-depth analysis of the relationship between tax revenue and infant mortality in Nigeria from 2004-2021. Descriptive statistics was employed to analyze the variables. While inferential statistics (Regression analysis) was used to test the hypothesis via the aid of E-View 9.0 statistical software. The result revealed that company income tax has a negative and insignificant effect on infant mortality rate in Nigeria. Therefore, it was recommended that the review of tax incentives to attract both local and foreign companies and investors by the Government in order to boost revenue consequently, address the mortality rate in the country by providing good healthcare services for the breast feeding mothers and their children.
Keywords: Company income tax; Infant mortality rate; Nigerian economy